Impacts of land use on the dynamics, stocks and physical fractions of soil organic matter in tropical ecosystems - Brito, Paulo Henrique Ferreira de (2025)
Soil organic matter (SOM) is a critical element for sustaining the fertility of tropical soils andaddressing climate change. However, the dynamics of SOM in response to changes in land useare still poorly understood, especially in highly threatened tropical ecosystems such as theAtlantic Forest. The main objective of this study was to evaluate the impact of different landuse systems on carbon (C), nitrogen (N) and sulfur (S) stocks and on the distribution of thephysical fractions of SOM, including particulate organic matter (POM), mineral-associatedorganic matter (MAOM) and dissolved organic matter (DOM), in representative areas of theAtlantic Forest in southeastern Brazil. The chapters of this work addressed the followingspecific aims: i) to review the theoretical framework and mechanisms governing the formation,persistence and dynamics of the physical fractions of SOM, highlighting knowledge gaps; ii)to quantify the stocks of C, N and S in different fractions of SOM at surface (0-5 cm) andsubsurface (50-60 cm) depths in different land use systems, including native forests, pasturesand agricultural crops; iii) to investigate SOM contents in order to understand the dynamics oforganic carbon and nutrient formation in tropical soils. The soils analyzed belong to the area ofthe Federal University of Viçosa (UFV), located in the Zona da Mata region of Minas Gerais,Brazil, with a tropical high-altitude climate (Cwa) and soils classified as typical dystrophicLatossolos Vermelho-Amarelos (Oxisols). Seven land-use systems were evaluated: nativeforest, Araucaria forest, Eucalyptus and rubber plantations, pasture, coffee and corn. Soilsamples were collected in representative trenches and subjected to analysis of the physicalfractionation of SOM, quantification of C, N and S stocks and chemical and physical soilcharacterization. The results showed that systems with perennial vegetation, such as nativeforests and Araucaria plantations, had higher stocks of C and N, especially in the more stablefractions (MAOM). On the other hand, agricultural systems, such as coffee and corn, resultedin lower SOM accumulation, especially in the more labile fractions (POM and DOM). Inaddition, C stocks in the subsoil were more homogeneous between the systems, suggesting thatsustainable management practices can mitigate carbon loss. This study contributes to theunderstanding of the impacts of changes in land use on the dynamics of SOM in tropicalecosystems and provides fundamental information for the development of public policies andmanagement practices that promote soil conservation, carbon sequestration and environmentalsustainability.